Determination of Value of Evapotraspiration and Plant Coefficient of IR64 Rice Variety (Oryza sativa L.) in the Faculty of Agriculture, University of Sumatera Utara Green House - Yunidar Nasution; Sumono Sumono; Ainun Rohana (Universitas Sumatera Utara, 2015)
The water requirement of rice crop is compose of saturation, percolation, flooding and evapotranspiration. The amount of evapotranspiration can be determined based on the value of potential evaporation and the rice crop coefficient values for each period of growth. This study was aimed to assess the value of evapotranspiration and coefficient of IR64 iice (var. Oryza sativa L.) in green house with inundation of 5 cm and 10 cm high. The results showed that the value of the coefficient of the rice plant at 5 cm water level was 0.96 in early growth phase, 0.88 in the phase of active growth, 0.84 in reproductive growth phase, and 0.56 in the ripening phase, while for the water level of 10 cm was 1.03 in the early growth phase, 1.10 in the active growth phase, 1.03 in reproductive growth phase, and 0.71 in the ripening phase. Average of rice productivity was 746.7 grains/plots for the water level 5 cm, and at 10 cm was 723.1 grains/plot. Inundation height of 5 cm could save water by 50% compared to 10 cm high inundation. Keywords: Evapotranspiration, green house, plant coefficient, rice